2012
DOI: 10.1080/08995605.2012.742843
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sensation Seeking and Need for Structure Before and After a Combat Deployment

Abstract: In this study, soldiers' adaptation with the situational demands on combat deployment is explored. Certain changes on the level of two needs-based personality characteristics, Sensation Seeking (SS) and Need for Structure (NS) take place across deployment: soldiers who are lower in SS were more inclined to seek for sensations after deployment, and soldiers at the extremes of the NS dimension, modified their behavioral tendencies after deployment towards a moderate level. According to our findings, these change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Of course, it is unclear if a causal interpretation is appropriate or, if so, what underlying mechanisms might account for these associations. Suggestions exist in the literature, such as that longer tenure of unit leaders is associated with both improved unit discipline (Shamir et al , 2000) and reduced aggression of unit members (Bliese et al , 2002), that the disciplinary climate created by unit leaders influences violence rates within units (Millikan et al , 2012), and that unit leaders who experience repeated deployments might become more tolerant of violence (Parmak et al , 2012). But systematic multivariate analysis and subsequent experimentation would be needed to determine which of these or other processes might account for the associations found here between unit leader tenure/experiences and unit member violent crimes.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, it is unclear if a causal interpretation is appropriate or, if so, what underlying mechanisms might account for these associations. Suggestions exist in the literature, such as that longer tenure of unit leaders is associated with both improved unit discipline (Shamir et al , 2000) and reduced aggression of unit members (Bliese et al , 2002), that the disciplinary climate created by unit leaders influences violence rates within units (Millikan et al , 2012), and that unit leaders who experience repeated deployments might become more tolerant of violence (Parmak et al , 2012). But systematic multivariate analysis and subsequent experimentation would be needed to determine which of these or other processes might account for the associations found here between unit leader tenure/experiences and unit member violent crimes.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Parmak, Euwema, and Mylle (2012), the focus was on changes in Sensation Seeking and Need for Structure from before to after a combat deployment. The study consisted of three rotations of Estonian male professional soldiers (n = 192) deployed to Afghanistan.…”
Section: Changes In Sensation Seeking From Before To After Deploymentmentioning
confidence: 99%
“…In Parmak, Mylle, and Euwema (2014), the focus was on Sensation Seeking and perceived Need for Structure in relation to soldiers' well-being before and after operational deployment. As in the study of Parmak et al (2012), the sample consisted of three rotations of professional soldiers deployed for a 6-month tour of duty to Afghanistan, however, the final sample included 167 soldiers in total. The results showed that well-being declined in the soldier sample as a whole after deployment, but the degree of decline differed depending upon personality profile.…”
Section: Changes In Sensation Seeking From Before To After Deploymentmentioning
confidence: 99%
“…1 Using excellent panel data with Estonian soldiers, the authors convincingly show that their findings are accurate. They fail, however, to provide an argument why this is the case.…”
Section: Introductionmentioning
confidence: 90%
“…In a Military Psychology article from 2012, Parmak, Euwema, and Mylle observe that soldiers' level of ''sensation seeking''increases during and following deployment. 1 Using excellent panel data with Estonian soldiers, the authors convincingly show that their findings are accurate. They fail, however, to provide an argument why this is the case.…”
Section: Introductionmentioning
confidence: 90%